(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The laws are aimed at protecting not only the interests of the state, but also the interests of the individual, the formation of confidence in the future customs officers, social and legal norms, respect for the law, the formation of legal skills and abilities of future customs officers, the fight against crime and their The issues of socio-legal culture and social activism in the minds of the people are among the most pressing issues of today. This article describes the basis for the formation of the legal culture of future customs officials through the functions of legal culture.